Absence in the Aftermath. (April 2017) - Kalman, Julie; Doron, Daniella
An estimated six million European Jews perished during the Second World War. Jews had been implanted right throughout Europe. Whether as integrated citizens, or as significant others, they contributed to the fabric of societies all over Europe in unique and significant ways. At the end of the war, much of Europe lay in waste. Yet almost all over the continent, societies were also forced to re-organize themselves to become places that no longer had a Jewish community. How were European narratives shaped and re-shaped around those great holes in the fabric of daily life? How did surviving Jews experience the absence of families, friends, and former national and ethnic communities? The scholarship of memory has established that the way that nations remember selectively can tell us about their processes of building national mythologies and identities. Presences, too, can be used and abused, calculated to evoke or elide a significant absence. The idea of absence gives us a framework for making sense of those traces. Thinking about the aftermath of the Second World War and the Holocaust in terms of absence offers new insight into the nature of postwar life in Europe and processes of rebuilding, of recasting national stories, and reimagining.